Two-level aggregation of Leontief model "input-output" - Liashenko, Olena I. (Publishing House of the Wrocław University of Economics, 2009)
Production and distribution of products in economy are connected by balance correlations which make a basis of all economic-mathematical models of process of reproduction. Any macromodel of economy as complete developing system can be considered as some set of macrocorrelations relative to macrovariables, that is a result of aggregation of the certain microcorrelations. Therefore it is urgent to develop the theory of aggregation of the economic descriptions, as the methods of aggregating are the tool of a substantiation of mathematical models of economy. So, the opening by W.W. Leontief of relative stability of proportions of interindustry inputs promoted distribution of models of economic growth. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 287-293